Purchase Profile of Hypertension Drugs of Calcium Channel Blocker Group Amlodipine Doses of 5 mg and 10 mg in Several Gorontalo City Pharmacies January - March period in 2024 - Paneo, Mohamad Aprianto; Thomas, Nurain Ain; Latif, Multiani S; Pido, Nur Huda (Universitas Negeri Gorontalo, 2024)
Hypertension is one of the most common diseases in Indonesia, one of which in the province of Gorontalo is included in the top 10 largest diseases. According to the health data profile from the Gorontalo provincial health office in 2022, the level of hypertension in Gorontalo city reached 2,325 cases, or around 4.6%. High cases of hypertension must be balanced with the provision of hypertension drugs, one of which is the calcium channel blocker (CCB) hypertension drug, amlodipine. The purpose of this study was to see the profile of purchasing hypertension drugs from the Calcium Channel Blocker (CCB) Amlodipine group in the community in Gorontalo City, especially in pharmacy and pharmaceutical service facilities. The research method uses a random sampling observation method, namely to see drug purchases in three Gorontalo city pharmacies located in different sub-districts. Purchase tracking was carried out in January, February, and March 2024. The results showed the purchase of amlodipine drugs in the three pharmacies in different amounts. Pharmacy B dominated the purchase of drugs compared to Pharmacy A and Pharmacy C at the 5 mg and 10 mg doses, respectively. Based on the results obtained, these differences are influenced by several indicators, including drug availability, drug completeness, pharmacy strategic location, and customer satisfaction.